Disrupted Structural Brain Network Organization Behind Depressive Symptoms in Major Depressive Disorder - Liu, Jing; Xu, Xiaopei; Zhu, Chunqing; Luo, Liyuan; Wang, Qi; Xiao, Binbin; Feng, Bin; Hu, Lingtao; Liu, Lanying (Frontiers in Psychiatry, 2020)
Major depressive disorder (MDD) is a severe and devastating condition. However, the anatomical basis behind the affective symptoms, cognitive symptoms and somatic-vegetative symptoms of MDD is still unknown. To explore the mechanism behind the depressive symptoms in MDD, we used structural brain connectivity analysis to investigate the network difference between MDD patients and healthy controls (CN), and to explore the association between network metrics and patients’ clinical symptoms. Twenty-six patients with MDD and 25 healthy controls were included. A baseline 24-item Hamilton rating scale for depression (HAMD-24) score ≥ 17 and seven factor (anxiety/somatization, weight loss, cognitive disturbance, diurnal variation, retardation, sleep disturbance, hopelessness) scores were assessed. When compared with healthy subjects, significantly higher characteristic path length and clustering coefficient as well as significantly lower network efficiencies were observed in patients with MDD. Furthermore, MDD patients demonstrated significantly lower nodal degree and nodal efficiency in multiple brain regions including superior frontal gyrus, supplementary motor area, calcarine fissure, middle temporal gyrus and inferior temporal gyrus. We also found that the characteristic path length of MDD patients was associated with weight loss. Moreover, significantly lower global efficiency of MDD patients was correlated with higher total HAMD score, anxiety somatization and cognitive disturbance. In conclusion, our results demonstrated that MDD patients had impaired structural network features compared to CN, and disruption of optimal network architecture might be the mechanism behind the depressive symptoms and emotion disturbance in MDD patients.